2019
DOI: 10.18502/tim.v4i1.1665
|View full text |Cite
|
Sign up to set email alerts
|

Eryngium heterophyllum and Amphipterygium adstringens Tea Effect on Triglyceride Levels; A Clinical Trial

Abstract: Herbal medicine represents an alternative for treating dyslipidemia. It has been probed that aerial part of Eryngium heterophyllum, a species of medicinal plant that belongs to the family Apiaceae, reduces cholesterol by 27% in rats. On the other hand, Amphipterygium adstringens, a Mexican tree exerts a significant hypocholesterolemic effect on rats, lowering cholesterol levels by 31%. The aim of this project was to evaluate the PC-300 tea (Eryngium heterophyllum egelm + Amphipterygium adstringens) against hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Cholesterol plays a vital role in maintaining cellular homeostasis in the body (34). Major dietary sources of cholesterol include red meat, processed meat, egg yolks, dairies, fish, butter, cheese, shrimp, and poultry (35). Considering that a highcholesterol diet might represent an unhealthy dietary pattern and lead to chronic diseases such as cancer and cardiovascular diseases (36,37), the relationship between dietary cholesterol and the risk of cancer has received much attention (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol plays a vital role in maintaining cellular homeostasis in the body (34). Major dietary sources of cholesterol include red meat, processed meat, egg yolks, dairies, fish, butter, cheese, shrimp, and poultry (35). Considering that a highcholesterol diet might represent an unhealthy dietary pattern and lead to chronic diseases such as cancer and cardiovascular diseases (36,37), the relationship between dietary cholesterol and the risk of cancer has received much attention (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that indeed the mechanism of serum cholesterol reduction was related to the inhibition of said enzyme, as in the case of statin drugs. In the same way, García-Gómez et al (2019) [ 65 ], in a 1-month clinical study, showed that combined treatment of E. heterophyllum and Amphipterygium adstringens with proven hypocholesterolemic activity tested in rats, reduced triglyceride levels by an average of 20%. On the other hand, Carreón-Sánchez et al (2013) [ 4 ] showed that the ethanolic extract of E. heterophyllum , after being administered to mice by oral gavage in a single dose of 100 mg/kg of weight in a volume of 0.2 mL/30 g, had no hypoglycemic effect or acute or chronic anti-inflammatory effect; nor did it cause visible toxic effects in the acute poisoning model in mice.…”
Section: Biological and Pharmacological Activitymentioning
confidence: 86%
“…Other components of E. carlinae are triterpene saponins, which played an important role in dyslipidemia by reducing the serum concentrations of lipids in mice ( 48 ). In another study, a group of rats were induced into diabetes and were given an ethanolic extract of E. carlinae and Atorvastatin both, separately and together, for 40 days ( 44 ).…”
Section: Literature Reviewmentioning
confidence: 99%